Pertumbuhan dan produksi kangkung darat (Ipomoea reptans Poir) pada berbagai dosis pupuk papua nutrient granule di Manokwari - Besse Amriati; Rizald Hussein; Sonita Naa; Saraswati Prabawardani; Hangrie Jimmy Namserna (Agrotek, 2021)
The aim of the study was to determine the apropriate dose of Papua Nutrient Granule fertilizer on the growth and production of kangkong (Ipomea reptans poir). The research was carried out at the screen house of the Faculty of Agriculture, University of Papua, Manokwari for 2 months from July to August 2019. The study was a single factor experiment using a Randomized Block Design. The treatment dose of Papua Nutrient Granule fertilizer consisted of control/Papua Nutrient Fertilizer 0 tons/ha), Papua Nutrient Fertilizer 5 tons/ha, Papua Nutrient Fertilizer 10 tons/ha), Papua Nutrient Fertilizer 15 tons/ha), Papua nutrient fertilizer 20 tons/ha. The results showed that the application of Papua Nutrient significantly affected the growth and yield of kangkong at all ages of observation. Papua Nutrient granule fertilizer with doses of 15 and 20 tons/ha produced height, rate of plant height, number of leaves and leaf growth rate, fresh stover weight and fresh root weight per plant better than other fertilization treatments and control.